Pengembangan Aplikasi Layanan Informasi Pers Menggunakan Agile (STUDI KASUS : PERS JEMPOL PNP PADANG) - Maharani, Zelvia Olga; Purnomo, Agus Sidiq (CV. Information Technology Training Center - Indonesia (ITTC), 2021)
Websites have a very important role because they provide various information. Websites are useful to make it easier for someone to find information, ranging from obsolete to the latest information. Websites provide information that is up to date and currently being discussed. Therefore, we need a system to make it easier to provide information to readers. The system created is designed by using Agile where this methods is used for software development in the sort term. In addition, there is a method for sorting the most viewed data by using the MFEP ( Multifactoring Evaluation Process ) method. This research can help information providers in providing information to readers quickly, well and in a more structured manner.